2018
DOI: 10.11152/mu-1582
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of cleft lip and cleft lip palate – a case series

Abstract: Aim: Orofacial clefts comprise cleft lip (CL) or cleft lip-palate (CLP) and are the most frequently encountered malformation of the facial region, accounting for approximately 1-2.2/1,000 live births. The aim of this study was to reveal the particularities regarding the prenatal diagnosis of orofacial clefts in a series of 11 cases diagnosed in a tertiary center.Material and methods: The study was performed in a tertiary diagnostic center for a period of 8 years (January 2010 – December 2017), on8125 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
5
0
4
Order By: Relevance
“…Success could be achieved via teaching the parents and providing support to face such challenges 10,11,12,13 . In this study the prenatal diagnosis was confirmed in 37% of the affected cases, that rate was coincide with several previous studies which showed a range from 19% to 70% with correspondence to the design of the study 14,15,16,17 .…”
Section: Discussionsupporting
confidence: 92%
“…Success could be achieved via teaching the parents and providing support to face such challenges 10,11,12,13 . In this study the prenatal diagnosis was confirmed in 37% of the affected cases, that rate was coincide with several previous studies which showed a range from 19% to 70% with correspondence to the design of the study 14,15,16,17 .…”
Section: Discussionsupporting
confidence: 92%
“…Todos os estudos presentes na atual revisão detectaram a importância do exame de ultrassonografia como uma ferramenta segura a ser aplicada durante o pré-natal e confirmaram seus impactos positivos para o planejamento de intervenções de uma equipe multidisciplinar após o nascimento do bebê. Dessa forma incentivando tais exames a continuarem a ser oferecidos durante o período gestacional (Jones, 2002;Tonni et al, 2015;Maarse et al, 2015;Loozen et al, 2015;James & Sclieder, 2016;Lakshmy et al, 2017;Marginean et al, 2018;Ko et al, 2020;Faure et al, 2020;Yan et al, 2022).…”
Section: Resultsunclassified
“…Further the prenatal ultrasound technique has developed fast during the last years and allows almost 100% detection of CL/P at the end of the 1st trimester of pregnancy. The manifestation of the lip (CL) alone can usually only been seen during the 2nd trimester in ultrasound examination ( 21 ). While 81.4% of mothers were very satisfied with the information they received at the time of pre-natal diagnosis, there were even 4 mothers complaining about “insufficient” information at this time.…”
Section: Discussionmentioning
confidence: 99%